Prosecutor’s Role in Prosecuting Cryptocurrency-Related Transnational Crimes - Komalasari, Rita (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2025)
This study, titled Prosecutor’s Role in Prosecuting Cryptocurrency-Related Transnational Crimes, aims to comprehensively analyze the crucial role of informal cooperation in addressing the challenges posed by cryptocurrency assets in transnational cases. It provides insights into how informal cooperation mechanisms among international stakeholders are vital for prosecutors in managing the complexities of cryptocurrency-related investigations. The study finds that informal cooperation is indispensable for prosecutors, offering strengths such as agility, flexibility, and effective information exchange. It also identifies weaknesses like information asymmetry and coordination issues. The analysis underscores the importance of enhancing collaborative relationships among international stakeholders and offers recommendations for improving informal cooperation mechanisms to better support prosecutorial efforts.